Teacher Self-Efficacy and Mental Health—Their Intricate Relation to Professional Resources and Attitudes in an Established Manual-Based Psychological Group Program - Muenchhausen, Sophia von; Braeunig, Matthias; Pfeifer, Ruth; Göritz, Anja S.; Bauer, Joachim; Lahmann, Claas; Wuensch, Alexander (Frontiers in Psychiatry, 2021)
Introduction: Teaching is considered a mentally challenging occupation. Teacher self-efficacy is a personal resource which buffers the experience of stress and may be important in maintaining mental health. The preventive intervention “Manual-Based Psychological Group Program for Teachers” (MBPGPT) was applied and evaluated state-wide to improve mental health of teachers. This study aims to investigate the intricate relation between teacher self-efficacy and mental health and their changes in the course of the intervention. Method: Using a single-group pre-post design, the relation between teacher self-efficacy and mental health was investigated in 742 teachers. Pre-post changes in teacher self-efficacy and their interaction with mental health were examined in a subsample of 171 teachers, who met the conservative inclusion criteria. In ancillary analyses, correlations with underlying changes in work-related behavior and experience patterns were analyzed to better understand the intricate link between teacher self-efficacy and mental health. Results: Teacher self-efficacy showed a significant, moderate correlation with mental health. Self-efficacy was moderately higher after the intervention than before the intervention, but independent of changes in mental health. Teacher self-efficacy was related to work-related psychological resistance and positive emotions. An increase in teacher self-efficacy was accompanied by an improvement in life satisfaction and distancing ability. A decrease in teacher self-efficacy went hand in hand with a reduced experience of social support. Discussion: This study confirmed teacher self-efficacy as an important, reliable resource and its correlation with psychological resistance. The absence of a control group limits what causal conclusions can be drawn from the study. Nevertheless, self-efficacy seems to be a worthwhile goal of preventive interventions for teachers and should be promoted due to its wide-ranging implications. Suggestions for further studies and interventions are made.